1992
DOI: 10.1557/jmr.1992.0450
|View full text |Cite
|
Sign up to set email alerts
|

The deformation behavior of ceramic crystals subjected to very low load (nano)indentations

Abstract: The ultra-low load indentation response of ceramic single crystal surfaces (Al2O3, SiC, Si) has been studied with a software-controlled hardness tester (Nanoindenter) operating in the load range 2–60 mN. In all cases, scanning and transmission electron microscopy have been used to characterize the deformation structures associated with these very small-scale hardness impressions. Emphasis has been placed on correlating the deformation behavior observed for particular indentations with irregularities in recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
229
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 531 publications
(255 citation statements)
references
References 25 publications
25
229
0
1
Order By: Relevance
“…Initial observations [6,7] and later extensive papers [12±16] have now dealt exclusively with the fact that nanoindentation can detect the onset of dislocation nucleation. While not nanoindentation, this was ®rst suggested by Gane and Bowden's [17] and Pethica and Tabor's [18] seminal experiments exhibiting yield instabilities of sharp gold point contacts via TEM [17] and resistivity [18] techniques.…”
Section: Dislocation Nucleationmentioning
confidence: 99%
“…Initial observations [6,7] and later extensive papers [12±16] have now dealt exclusively with the fact that nanoindentation can detect the onset of dislocation nucleation. While not nanoindentation, this was ®rst suggested by Gane and Bowden's [17] and Pethica and Tabor's [18] seminal experiments exhibiting yield instabilities of sharp gold point contacts via TEM [17] and resistivity [18] techniques.…”
Section: Dislocation Nucleationmentioning
confidence: 99%
“…Typical loads lie between 0.1 and 10 N, with indentation diameters of about 10-100 m, which are measured with sufficient accuracy by optical microscopy. A different approach is to measure the penetration depth of the indenter by using microdisplacement transducers of great accuracy (5). In this case, typical loads lie between 10 Ϫ5 and 10 Ϫ2 N. At this level, microhardness measurements reveal that for metals, the hardness tends to increase as the size of the indenter is reduced (6); this is attributed to the limited range of dislocation movement available when very small volumes are involved.…”
mentioning
confidence: 99%
“…Nevertheless, there were no significant discontinuities observed in unloading (except for pop-ins ) in loading portion are shown by arrows in figure 4. For some of the conventional metals it has been shown that discontinuities in the loading portion of nanoindentation is an indication of dislocation nucleation and/or movement [10]. Nevertheless, in this experiment, for the aged sample, A Sample, such explanation is not valid as the final depth of indent for the indents with maximum load close to zero and there is no trace of permanent deformation on the surface of material.…”
Section: Nanoindentationmentioning
confidence: 63%